VERIFICATION AND USABILITY ANALYSIS OF MEDIUM RANGE WEATHER FORECAST FOR THE KOKRAJHAR DISTRICT OF LOWER BRAHMAPUTRA VALLEY ZONE OF ASSAM - KULDIP MEDHI; KUSHAL SARMAH; VINOD UPADHYAY; SUNIL KUMAR PAUL; ATHAR N. ISLAM; BIKASH J. GHARPHALIA (The Bioscan, 2020)
The moderated weather forecast received from the Regional Meteorological Centre (RMC), Guwahati for Kokrajhar district of Assam during March, 2014 to February, 2019 has been analyzed and verified for its accuracy with the observed weather parameters. The ratio score was found moderate to very good for daily rainfall forecast with highest for winter (91.4%) and lowest for pre-monsoon (67.2%) season. Rainfall forecast was poor during monsoon season with percentage of usability 31.0 per cent to 37.8 per cent with higher RMSE i.e., 30.6 to 45.2 mm as compared with pre-monsoon, post-monsoon and winter season with RMSE 13.5 to 20.8 mm, 2.3 to 17.9 mm and 0.6 to 3.1 mm, respectively. Performance of maximum and minimum temperature forecast was found relatively higher during post-monsoon and monsoon season with usability percentage varies from 62.3 per cent to 85.2 per cent and 69.7 per cent to 88.5 per cent, respectively. For morning and afternoon relative humidity forecast, usability percentage was very good during monsoon and post-monsoon season which varies from 99.1 per cent to 100 per cent and 85.2 per cent to 96.7 per cent, respectively. The correlation study reveals significant association between forecasted and observed weather parameters in most of the season. Overall, the forecast was found widely applicable for all the parameters on seasonal as well as annual basis.